2022
DOI: 10.1101/2022.10.24.513632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Three Variants of SARS-CoV-2in vivoShows Host-Dependent Pathogenicity in Hamsters

Abstract: Animal models are used in preclinical trials to test vaccines, antivirals, monoclonal antibodies, and immunomodulatory drug therapies against SARS-CoV-2. However, these drugs often do not produce equivalent results in human clinical trials. Here, we show how different animal models infected with some of the most clinically relevant SARS-CoV-2 variants, WA1/2020, B.1.617.2/Delta, B.1.1.529/Omicron and BA5.2/Omicron, have independent outcomes. We show that in mice, B.1.617.2 is more pathogenic, followed by WA1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The viral burden also started dropping down in the nasal regions at 4 dpi, causing less penetrable to the lungs in the case of Omicron infection at 4 dpi which further explains its lower replication efficiency as opposed to the Delta variant. These data were consistent with earlier observations studied on hamsters (21). The earlier in vitro comparative studies on growth kinetics of the Delta and Omicron variants in Calu3 cells, a lung epithelial cell line, have shown that the Omicron has a poor replication rate which correlates with our findings of low lung viral copy number observed in Omicron infected hamsters (22).…”
Section: Discussionsupporting
confidence: 93%
“…The viral burden also started dropping down in the nasal regions at 4 dpi, causing less penetrable to the lungs in the case of Omicron infection at 4 dpi which further explains its lower replication efficiency as opposed to the Delta variant. These data were consistent with earlier observations studied on hamsters (21). The earlier in vitro comparative studies on growth kinetics of the Delta and Omicron variants in Calu3 cells, a lung epithelial cell line, have shown that the Omicron has a poor replication rate which correlates with our findings of low lung viral copy number observed in Omicron infected hamsters (22).…”
Section: Discussionsupporting
confidence: 93%